MELIHAT KEMBALI RADIKALISME ISLAM DI INDONESIA DAN UPAYA-UPAYA PENCEGAHANNYA - Turmudi, Endang (Jurnal Masyarakat dan Budaya, 2015)
Radicalism embraced by a smallgroup of Muslims in Indonesia continues to develop and their radical actions increased significantly, as can be seen from the bombing of some hotels, churches and even mosques. Radicalism is influenced by an ideology which among others opposes the presence o f(Secular) Indonesian States, considers other Muslims outside their own group as infidels and exerts to establish an Islamic state. Furthermore, the radicals tolerate violence and even terrorism in order to achieve what they pursue. Since radicalism deals with ideology, the effort of de-radicalization is to unplug certain Islamic understanding of the radicals. Without such direction, deradicalization seems to be difficult to achieve, given the fact that changing ideology is impossible. Therefore, experts proposed a program of "disengagement" which is“not to the point" trying to pull out the idea of radicalism. Nevertheless, the facts show that there has been some radical group exponents, such as AliImran, who are deradicalized, realizing what they did concerned with terrorism is wrong. From there, the government launched deradicalization programs involving many stakeholders. However, the effectiveness of the programs should be reviewed, and some research need to be conducted to see their constraints since the programs are not related to de-radicalize the terrorists only but also those embraced radicalism in general who are influenced by activist of social movements that propagate radicalism.